Islam and Gender: Media Construction in Television Drama Series Para Pencari Tuhan on SCTV - Rodiyah, Nuning (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study examines gender equality and the principles of Islamic teachings in the TV drama series Para Pencari Tuhan. The purpose of this study is to outline how the drama series' plots and visuals portray Islam and gender narratives. The Social Construction Theory of Peter L. Berger and Thomas Luckmann, and theory of Gender Injustice of Mansour Fakih's serve as the foundational framework. Based on Muhammad Quraish Shihab's main concepts of Islamic teachings, the three primary principles of Islam are: aqidah, or belief; sharia, or experience of legal requirements; and akhlaq, or manners. This qualitative study used Norman Fairclough's discourse analysis approach, while data collection techniques were carried out by watching thirty episodes of the TV drama series Para Pencari Tuhan season 16 three times and interviewing the production team and correlated informants. The results of this research show that the basic values of Islamic teachings are conveyed through the narrative elements (storyline) and cinematic elements (setting, audio and appearance of the characters) of the series. Meanwhile, gender equality is shown through female characters who experience injustice. It is also shown that Women actually have potential and qualities that are no less than men. Mass media, including TV drama series, can be a means of conveying positive da'wah messages about Islam and gender equality. Until now, television is still an alternative media besides the internet, for people who want to find entertainment.